2004
DOI: 10.1063/1.1841470
|View full text |Cite
|
Sign up to set email alerts
|

An organic thin-film transistor of high mobility by dielectric surface modification with organic molecule

Abstract: Organic thin-film transistors (OTFTs) based on pentacene semiconductor are elaborated on the plastic substrates through a four-level mask process without photolithographic patterning to yield a simple fabrication process. Octadecyltrimethoxysilane (OTMS) as an organic molecule for self-assembled monolayers is deposited on the surface of zirconium oxide dielectric layer. The effect of OTMS interlayer with gate dielectric surface modification on the field effect mobility of OTFTs has been examined and these prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 18 publications
0
40
0
2
Order By: Relevance
“…The use of SAMs comprising different functional groups and chemical bonding schemes to gate oxides is a common technique, including silane or phosphonate derivatives. [178][179][180][181] It should be kept in mind that any surface modification will most likely result in a different organic semiconductor film quality (in terms of crystallinity and density of defects, see below), thus leading to variations of device performance.…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…The use of SAMs comprising different functional groups and chemical bonding schemes to gate oxides is a common technique, including silane or phosphonate derivatives. [178][179][180][181] It should be kept in mind that any surface modification will most likely result in a different organic semiconductor film quality (in terms of crystallinity and density of defects, see below), thus leading to variations of device performance.…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…We follow ref. [31] and calculate the light quark part of the correlation function in the coordinate-space, which is then Fourier transformed to the momentum space in D dimensions. The resulting light-quark part is combined with the charm-quark part before it is dimensionally regularized at D = 4.…”
mentioning
confidence: 99%
“…Halik et al [1] demonstrated that large operating voltages were not an intrinsic feature of organic transistors, and the operating voltages and power dissipations of organic devices could be dramatically reduced by using extreme thin self-assembly film of silane-based molecular as dielectric. Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14]. Until now, the reported high-k materials used in OFETs include HfO 2 [3], Al 2 O 3 [4], Barium Zirconate Titanate (BZT) [5], BZN (Bi 1.5 Zn 1.0 Nb 1.5 O 7 ) [6], SBT (SrBi 2 Ta 2 O 9 ) [7], Ta 2 O 5 [8], TiO 2 [9], and ZrO 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%